Early administration of RS 67333, a specific 5-HT4 receptor agonist, prevents amyloidogenesis and behavioral deficits in the 5XFAD mouse model of Alzheimer’s disease - Giannoni, Patrizia; Gaven, Florence; De Bundel, Dimitri; Baranger, Kevin; Marchetti-Gauthier, Evelyne; Roman, François S.; Valjent, Emmanuel; Marin, Philippe; Bockaert, Joël; Rivera, Santiago; Claeysen, Sylvie (Frontiers in Aging Neuroscience, 2013)
Amyloid β (Aβ) accumulation is considered the main culprit in the pathogenesis of Alzheimer's disease (AD). Recent studies suggest that decreasing Aβ production at very early stages of AD could be a promising strategy to slow down disease progression. Serotonin 5-HT4 receptor activation stimulates α-cleavage of the amyloid precursor protein (APP), leading to the release of the soluble and neurotrophic sAPPα fragment and thus precluding Aβ formation. Using the 5XFAD mouse model of AD that shows accelerated Aβ deposition, we investigated the effect of chronic treatments (treatment onset at different ages and different duration) with the 5-HT4 receptor agonist RS 67333 during the asymptomatic phase of the disease. Chronic administration of RS 67333 decreased concomitantly the number of amyloid plaques and the level of Aβ species. Reduction of Aβ levels was accompanied by a striking decrease in hippocampal astrogliosis and microgliosis. RS 67333 also transiently increased sAPPα concentration in the cerebrospinal fluid and brain. Moreover, a specific 5-HT4 receptor antagonist (RS 39604) prevented the RS 67333-mediated reduction of the amyloid pathology. Finally, the novel object recognition test deficits of 5XFAD mice were reversed by chronic treatment with RS 67333. Collectively, these results strongly highlight this 5-HT4 receptor agonist as a promising disease modifying-agent for AD.